2010
DOI: 10.1016/j.actbio.2010.06.020
|View full text |Cite
|
Sign up to set email alerts
|

In vivo short-term and long-term host reaction to starch-based scaffolds

Abstract: The implantation of biomaterials may elicit a host response to this foreign body, and the magnitude of that reaction depends on the host and on the implanted material. The aim of this study was to compare the inflammatory response induced by the implantation of starch-based (SPCL) scaffolds in two implantation rat models: subcutaneous (SC) and intramuscular (IM). Moreover, two methodologies, wet spinning (WS) and fibre-bonding (FB), were used to prepare the scaffolds. The short-term inflammatory/immune host re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 40 publications
(53 reference statements)
0
31
0
Order By: Relevance
“…HUVECs can be cultured on a SPCL scaffold resulting in capillary-like structures and expression of endothelial specific markers [85,86]. However, SPCL induces a moderate inflammatory reaction following subcutaneous and intramuscular implantation [87]. SPCL is susceptible to enzyme degradation by α-amylase and lipase which can facilitate the enzymatic hydrolysis of SPCL both in vitro and in vivo [88].…”
Section: Starchmentioning
confidence: 99%
“…HUVECs can be cultured on a SPCL scaffold resulting in capillary-like structures and expression of endothelial specific markers [85,86]. However, SPCL induces a moderate inflammatory reaction following subcutaneous and intramuscular implantation [87]. SPCL is susceptible to enzyme degradation by α-amylase and lipase which can facilitate the enzymatic hydrolysis of SPCL both in vitro and in vivo [88].…”
Section: Starchmentioning
confidence: 99%
“…The use of starch based materials in biomedicine could be limited by the host immune response towards the starch-based tool in contact with cells and tissues [16]. Specific immune response is elicited by the direct interaction between the material surface and the immune cell surface or as a secondary effect due to the molecular immune factors absorbed onto the material, once in the host body.…”
Section: Page 4 Of 26mentioning
confidence: 99%
“…This is in full agreement with previous studies conducted in long-term implantation using SPCL fiber meshes, where the final data found suggested a good integration of the materials in the host with a normal progress of the reaction for all condition studied. 22 X-ray images obtained after the surgery and on the day of euthanasia, demonstrated that the choice of primary bone fixation device was correct. Furthermore, the X-ray results confirm that during the time of the study there was no bone union among the proximal/ distal bone fragments in all the study animals, and that it was only possible to visualize radiographically bone formation in both proximal/distal bone fragments, in the defects treated with constructs cultured in the bioreactor, upon 12 weeks of implantation The critical defects implanted with GBMSCs-SPCL constructs can be compared to a complicated comminuted fracture in which the fracture site is unlikely to contribute substantially to the transfer of load during weight-bearing, and thus the plate must essentially support all of the forces transmitted through the limb.…”
Section: Discussionmentioning
confidence: 94%